Factors Related to the Utilization of Health Services in the Outstanding Unit in the Regional General Hospital of Buton North Regency - Syafruddin, Syafruddin; Saafi, La Ode; Azizi Jayadipraja, Erwin; Supodo, Timbul; Sunarsih, Sunarsih (Waluya The International Science of Health Journal, 2022)
Introduction: Service utilization is the use of service facilities provided either in the form of outpatient care, inpatient care, home visits by health workers or other forms of utilization of these services based on the availability and continuity of services, public acceptance and fairness, easily accessible by the community, affordable, and quality. Method: This research is quantitative research with a cross-sectional study design. The population in this study amounted to 352 respondents. The sample size is 187 respondents. Result: The average significance of respondents to four variables, the variable of health service availability is 0.000, the variable of access to health services is 0.002, the variable is cost affordability, the value is 0.000, the variable of Service Acceptance is 0.000. Of the four variables have a relationship with the utilization of outpatient health services. Conclusion: The average the four variables with the level of trust that exists based on the significance number has factors related to the utilization of health services which are quite closely related to the condition and situation of hospital services when patients make visits.